Beelzebub in India and Tibet. Issue 2 (1st February 2022) - Pittman, Michael
Abstract : One of the overarching themes of G. I. Gurdjieff's magnum opus, All and Everything, or Beelzebub's Tales to His Grandson, is the soul and its development. This essay will consider comments on the soul, and related terms, as they are presented in two early chapters relating Beelzebub's travels to Indian and Tibet. The concepts of monasticism, Prana, the destructive figure of the Hasnamuss (the antithesis of saints and messengers) as well as the significance of the organ Kundabuffer are addressed in some detail. Here, Gurdjieff provides initial indications that the soul is not a given. Rather, the soul is created because as a result of spiritual efforts and transformation. In the critique of the failings and foibles of humans, the notion of the soul is exhumed and often excoriated. Yet, revealed in these passages is a picture of the potential for the human being, and the important role that humans may play in the Universe.